2019
DOI: 10.2337/dc19-0009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Fast-Acting Insulin Aspart Compared With Insulin Aspart, Both in Combination With Insulin Degludec, in Children and Adolescents With Type 1 Diabetes: The onset 7 Trial

Abstract: To confirm efficacy and safety of fast-acting insulin aspart (faster aspart) versus insulin aspart (IAsp), both with basal insulin degludec, in a pediatric population with type 1 diabetes. RESEARCH DESIGN AND METHODSAfter a 12-week run-in, this treat-to-target, 26-week, multicenter trial randomized participants (1 to <18 years) to double-blind mealtime faster aspart (n = 260), mealtime IAsp (n = 258), or open-label postmeal faster aspart (n = 259). The primary end point was change from baseline in glycated hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(92 citation statements)
references
References 21 publications
4
75
0
13
Order By: Relevance
“…Expectedly, superiority in HbA 1c reduction ( Table 1) and improvement of 2.48 mmol/L in average self-measured 2-h PPG for all meals were shown for faster aspart versus basal-only therapy, with a several-fold higher rate of severe or BG-confirmed hypoglycaemia when adding faster aspart to basal insulin ( Table 1). The efficacy and safety of faster aspart were also evaluated in children and adolescents (1-17 years) with T1D in a 26-week trial with faster aspart or IAsp in a basal-bolus regimen with insulin degludec [35]. PPG increment at 1 h, based on self-measured BG, was reduced for faster aspart versus IAsp at breakfast, dinner and across all meals, and HbA 1c was reduced by 0.17% for faster aspart versus IAsp, with a comparable overall rate of severe or BG-confirmed hypoglycaemia [35].…”
Section: Multiple Daily Injection Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Expectedly, superiority in HbA 1c reduction ( Table 1) and improvement of 2.48 mmol/L in average self-measured 2-h PPG for all meals were shown for faster aspart versus basal-only therapy, with a several-fold higher rate of severe or BG-confirmed hypoglycaemia when adding faster aspart to basal insulin ( Table 1). The efficacy and safety of faster aspart were also evaluated in children and adolescents (1-17 years) with T1D in a 26-week trial with faster aspart or IAsp in a basal-bolus regimen with insulin degludec [35]. PPG increment at 1 h, based on self-measured BG, was reduced for faster aspart versus IAsp at breakfast, dinner and across all meals, and HbA 1c was reduced by 0.17% for faster aspart versus IAsp, with a comparable overall rate of severe or BG-confirmed hypoglycaemia [35].…”
Section: Multiple Daily Injection Therapymentioning
confidence: 99%
“…Several faster aspart formulations with different combinations of niacinamide and zinc concentrations were tested in a clinical pharmacology trial, and, [16][17][18][19][20][21][22][23][24][25][26][27]. Moreover, phase III trials have investigated the efficacy and safety of faster aspart versus IAsp in subjects with T1D or T2D [28][29][30][31][32][33][34][35]. This review summarises the results from clinical pharmacology trials with faster aspart and relates these findings to the clinical benefits associated with faster aspart compared with IAsp based on outcomes from the phase III trials.…”
Section: Introductionmentioning
confidence: 99%
“…Trials in people with T2DM show a similar but lesser, yet statistically significant, reduction in the 1‐h PPG increment (mean decrease −0.40 to −0.59 mmol/L) compared with aspart . Despite reducing PPG levels in the trials reported, the overall glucose‐lowering ability of faster aspart compared with aspart (based on HbA1c levels) was comparable in T2DM or slightly better in T1DM . SMPG profile data in several trials indicate that faster aspart has a minimal effect on reducing PPG after mixed meals.…”
Section: What Is the Potential Role For The Second‐generation Of Rapimentioning
confidence: 85%
“…Eight phase 3 trials have reported the efficacy and safety of faster aspart (Table ) . Seven phase 3 trials are evaluating the efficacy and safety of ultra‐rapid lispro versus lispro, with preliminary results for three of these trials reported as abstracts .…”
Section: Second Generation Rapid‐acting Insulin Analoguesmentioning
confidence: 99%
See 1 more Smart Citation